Effectiveness of Smoke-Free Area (KTR) Policy in Schools: A Study on High School and Vocational School Students in Padang City - Iqbal, Wira; Azmi, Fadilla (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
Adolescent smoking behavior poses a serious challenge to public health. This study aims to analyze the effectiveness of the Smoke-Free Area (SFA) policy in two high schools in Padang City. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation involving 37 students from Senior High School X and Vocational High School Y West Sumatera. The study findings revealed that although most students support the SFA policy, there is still inconsistency between their attitudes and actual behavior, mainly due to the lack of teacher role models and limited visibility of the policy. This study concludes that the success of the SFA policy depends not only on formal regulations but also on consistent implementation and active involvement of the entire school community. Participatory approaches and behavioral modeling are the main strategies for the policy's success in the educational environment.